Effect Of Systemic And Local Immunomodulation Therapies On Conception Rate In Endometritic Cows - Biswal, S. S.; Das, S.; Mohanty, D. N.; Jena, D. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was carried out to evaluate the efficacy of different immunomodulators by evaluating its effect on PMN cells, blood biochemical parameters and conception rate in 21 endometritic cows. The cows were randomly assigned into three groups (n=7) and treated with three different immunomodulators (Oyster glycogen 5 g i/ut once; Levamisole 10 ml s/c thrice, and PGF2α 500 µg once i/m), while seven healthy cows at estrus were taken as control. Cervical mucus samples were collected from all the animals and subjected to PMN cell count. Besides, serum samples were analyzed for total protein, albumin, AST and ALT. Conception rate was assessed following different immunomodulation therapies. There were significant differences (p<0.01) in PMN cell counts and AST level between before and after treatments. However, no significant variations (p<0.01) were observed for protein, albumin and ALT level before and after treatment. The conception rate was 57.14, 42.84, 42.84 and 71.42 % for Oyster glycogen, Levamisole, PGF2α and Control groups, respectively.